Market Frictions and Stock Market Performance in Nigeria - Adelowotan, Michael O.; Oshadare, Segun A.; Idolor, Joseph E. (Acta Universitatis Danubius. Œconomica, 2022)
What comes to mind when we hear the phrase “financial market frictions” are taxes and transactions costs which are obvious examples, but market frictions are diverse and widespread. This paper models the various components of financial market friction and how they affect the Nigerian capital market with emphasis on variables like transaction cost, taxes and regulations, asset indivisibility, non-traded asset and agency with information problems. The study employed use of econometric analysis like unit root test, co-integration test, correlation and regression with time series data from 1981-2018. It was discovered that the various components affect the stock market performance in different ways and also are real determinants of the various responses to issues in the stock market. Considering the results of econometric analysis, the study recommended among others proper management of the transaction costs, while the taxes paid by investors in the country should provide opportunity for investment and the capital market should operate in such a way as to make access to information valid while the number of instruments traded on the stock exchange should be increased to make investors have options.